Reconnection-generated Plasma Flows in the Quasi-separatrix Layer in Localized Solar Corona - Mondal, Sripan; Srivastava, Abhishek K.; Mishra, Sudheer K.; Sangal, K; Kayshap, Pradeep; Guo, Yang; Pontin, David I; Uritsky, Vadim M.; Ofman, Leon; Wang, Tongjiang (Institute of Physics, 2023)
Multiwavelength observations of the propagating disturbances (PDs), discovered by Atmospheric Imaging Assembly (AIA) on board Solar Dynamics Observatory (SDO), are analyzed to determine their driving mechanism and physical nature. Two magnetic strands in the localized corona are observed to approach and merge with each other, followed by the generation of brightening, which further propagates in a cusp-shaped magnetic channel. Differential emission measure analysis shows an occurrence of heating in this region of interest. We extrapolate potential magnetic field lines at coronal heights from the observed Helioseismic and Magnetic Imager vector magnetogram via Green’s function method using MPI-AMRVAC. We analyze the field to locate magnetic nulls and quasi-separatrix layers (QSLs), which are preferential locations for magnetic reconnection. Dominant QSLs including a magnetic null are found to exist and match the geometry followed by PDs; therefore, this provides conclusive evidence of magnetic reconnection. In addition, spectroscopic analysis of Interface Region Imaging Spectrograph Si iv λ1393.77 line profiles show a rise of line width in the same time range depicting the presence of mass motion in the observed cusp-shaped region. PDs are observed to exhibit periodicities of around 4 minutes. The speeds of PDs measured by the surfing transform technique are close to each other in four different SDO/AIA bandpasses, i.e., 304, 171, 193, and 131 Å, excluding the interpretation of PDs in terms of slow magnetoacoustic waves. We describe comprehensively the observed PDs as quasiperiodic plasma flows generated as a result of periodic reconnection in the vicinity of a coronal magnetic null.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Quasi-separatrix Layer; Plasma Flows; Localized Solar Corona